Online courses and ICT in education : emerging practices and applications - Tomei, Lawrence A. (Hershey PA : Information Science Reference, 2011)
'This book offers a critical review of current research in technology-supported education, focusing on the development and design of successful education programs, student success factors, and the creation and use of online courses'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references and index.
Keywords: Computer-assisted instruction; Internet in education; Distance education; Educational technology; Telecommunication in education; Education -- Effect of technological innovations on